Surgical and Orthodontic Management of Multiple Supernumerary and Impacted Teeth: A Case Report - Chaudhary, Nabin Kumar; Singh, Sunil Kumar; Chaudhary, Suvin (Nepal Journal of Health Sciences, 2026)
Abnormal upper anterior teeth in a young patient are often a source of esthetic concern for both the child and their parent. The 12-year-old male patient reported with an unesthetic smile with four supernumerary teeth and an impacted upper left maxillary central incisor. This case report describes combined surgical and orthodontic treatment for the removal of multiple supernumerary teeth, followed by orthodontic traction of the impacted incisor to guide it into its correct position, enhancing smile esthetics. The surgical orthodontic approach is the optimal strategy for treating impacted maxillary central incisors.